CXCL7 enhances RANKL-induced osteoclastogenesis via the activation of ERK/NFATc1 signaling pathway in inflammatory arthritis - Xinyu Wang; Lin Sun; Zhuo An; Changhong Li; Jinxia Zhao (Arthritis Research & Therapy, 2025)
Abstract Background Rheumatoid arthritis (RA) with anti-citrullinated protein/peptide antibodies (ACPA + RA) demonstrates more significant radiographic damage compared to ACPA-negative RA (ACPA- RA). Chemokine-activated signaling pathways contribute to the regulation of the bone formation and resorption. The potential role of C-X-C motif chemokine ligand 7 (CXCL7) in bone erosion and its viability as a therapeutic target for RA merit further investigation. Methods Plasma CXCL7 concentration was quantified using enzyme-linked immunosorbent assay (ELISA). The effect of CXCL7 on receptor activator of NF-κB ligand (RANKL)-induced osteoclastogeneis was assessed through tartrate-resistant acid phosphates (TRAP) staining and F-actin ring immunofluorescence. Western blotting analysis was used to identify the signaling pathways activated by CXCL7. To investigate the potential therapeutic effect by targeting Cxcl7, Cxcl7 neutralizing antibodies were administrated intraperitoneally to mice with collagen-induced arthritis (CIA). Histopathology and micro-computed tomography (micro-CT) scanning were utilized to assess joint inflammation and bone destruction in CIA mice. Results The plasma CXCL7 concentration was significantly higher in ACPA + RA compared with ACPA- RA and healthy controls. The level of CXCL7 was positively correlated with disease activity and bone erosion in RA patients. It was discovered that CXCL7 promoted RANKL-induced osteoclastogenesis in CD14 + monocytes derived from RA patients. Mechanistically, the addition of Cxcl7 significantly enhanced RANKL-induced phosphorylation of ERK1/2 and NFATc1 expresssion. Cxcl7 neutralizing antibody alleviated arthritis severity in CIA by reducing the inflammatory response, osteoclasts numbers, and bone destruction in CIA mice joints. Conclusion CXCL7 contributes to the bone erosion in RA by enhancing RANKL-induced osteoclastogenesis via the activation of ERK/NFATc1 signaling pathways. CXCL7 could potentially be targeted for therapeutic interventions in RA.